India in transition - "Jannuzi, F. Tomasson" (London, 1989)
I believe that it should be standard in the social sciences for an author to identify the personal valuations and assumptions that condition or qualify his work. By this means he can give his readers a sense of his motivation and biases, providing them a basis for interpreting the context that informs the work. What follows is my attempt to enable readers to trace the origins of my approach and arguments.
Keywords: Political economy